A Comparative Study on Drying of Ber - Das, Priyanka; Dutta, Archana Singha (Journal of Agricultural Engineering, 2014)
Ber (Zizyphus jujuba) is one of the popular seasonal, but highly perishable fruit of India. Plantations of indigenous fruit are depleting gradually due to lack of processing facilities. Traditional processing of the fruit, although crude, is popular in India. Traditionally processed fruits do not have market value as not accepted by the consumers. Among the unit operations for processing of fruit, drying is the most important. At domestic level, sun drying is popular and convenient, but does not maintain quality of the finished product. For commercial products mechanical dryers, solar dryers, microwave dryers, etc are used. Application of a dryer for a particular produce depends on the physical and biological characteristics of the produce. A study on drying pattern and nutritional qualities of dried product (ber) showed that microwave technology combined with solar drying could be applied to dry it and retain its quality.